Studi Psikometrik pada Skala Pengukuran Mathematical Resilience Calon Guru: Confirmatory Factor Analysis - Maulyda, Mohammad Archi; Hidayati, Vivi Rachmatul (Griya Journal of Mathematics Education and Application, 2025)
This study aims to test an instrument measuring the mathematical resilience of prospective elementary school teachers using a psychometric approach. The primary goal of this research is to evaluate the validity and reliability of the instrument using Confirmatory Factor Analysis (CFA), focusing on four key dimensions: value, struggle, growth, and culture. Data were collected from 204 prospective elementary school teachers at higher education institutions in Indonesia. The analysis results, using JASP with the Maximum Likelihood estimator, show that the instrument has good convergent validity with an Average Variance Extracted (AVE) value greater than 0.50 for most dimensions, as well as adequate reliability with omega and alpha coefficients above 0.70. The Heterotrait-Monotrait Ratio (HTMT) test also demonstrates good discrimination between dimensions. These findings provide significant contributions to the development of a valid and reliable instrument for measuring mathematical resilience in prospective teachers, which in turn can help improve mathematics teaching at the elementary education level.